Traditional Games as Alternative Activities for Children Stimulation - Putu Nugrahaeni Widiasavitri; Ni Made Yanti Ary Agustini; Dewi Puri Astiti; Luh Made Karisma Sukmayanti Suarya; Tuningsih Haryati (Journal of Psychology and Instruction, 2020)
In the span of one year, there has been an increasing number of complaints from parents and teachers about the adverse effects of gadgets. Complaints of the detrimental impacts of gadget addiction include children becoming lazy, irritable, lacking independence, irresponsible with schoolwork, and having shorter attention span compared to similar-aged children. The increasing number of complaints from parents and school teachers regarding the behaviour of students who are addicted to gadgets became the reason for the team to reintroduce traditional game play activities with friends and teachers in school. Several studies have shown that traditional games have numerous benefits, particularly to stimulate children's cognitive, social, and personality development. Therefore, the team strived to provide alternative games for students so as to help students reap the benefits of playing. The result of this activity indicates that traditional games could be alternative games to gadgets, which are beneficial for affective, cognitive, and motor development of children and act as the means to introduce children to the norms upheld in the society. To optimize the development of affective, cognitive, motor skills, and instill the norms in society, utilizing traditional games needs to be done by the school.